Traveling in randomly embedded random graphs. Issue 3 (14th December 2018) - Frieze, Alan; Pegden, Wesley
Abstract : We consider the problem of traveling among random points in Euclidean space, when only a random fraction of the pairs are joined by traversable connections. In particular, we show a threshold for a pair of points to be connected by a geodesic of length arbitrarily close to their Euclidean distance, and analyze the minimum length Traveling Salesperson Tour, extending the Beardwood‐Halton‐Hammersley theorem to this setting.